Adherence to initial exclusive breastfeeding among Chinese born and native Spanish mothers - Juana María Aguilar-Ortega; Juan Luis González-Pascual; César Cardenete-Reyes; Carmen Pérez-; Santiago Pérez-García; Laura Esteban-Gonzalo (BMC, 2019)
Abstract Background Benefits of breastfeeding on the health of children, mothers and society are well known. However, breastfeeding rates vary according to the population examined. Chinese-born women migrated to high-income countries have shown low breastfeeding rates. Nevertheless, studies comparing breastfeeding rates of Chinese-born immigrants and natives are scarce. The aims of this study were therefore: 1) to compare the rate of exclusive breastfeeding at hospital discharge after giving birth between Chinese-born women resident in Spain and native Spanish women, 2) to assess the influence of the biological, socioeconomic, work-related and cultural factors on exclusive breastfeeding in women of Chinese origin. Methods A cross-sectional descriptive study with between group comparisons. This study included 73 postpartum women (33 Chinese-born and 40 native Spanish women). The association between exclusive breastfeeding and the country of origin was assessed by binary logistic regression. Results Native Spanish women showed a greater prevalence of exclusive breastfeeding (80%) compared to Chinese born immigrant women (36.4%) (adjusted for socioeconomic status, parental level of education, age, cesareans and birth weight) (OR = 0.21; 95% CI 0.05-0.91; p = 0.037). However, in other models that considered both work and cultural influences, no differences were observed. Discussion The classic biological and socioeconomic variables (educational and socioeconomic levels) do not seem to explain the lower rates of exclusive breastfeeding among Chinese immigrant women. This paradigm of inequity appears to be based on both the work conditions as well as cultural characteristics of Chinese born women in Spain, such as their overall attitude towards breastfeeding.